2018
DOI: 10.1093/emph/eoy031
|View full text |Cite
|
Sign up to set email alerts
|

Variation among populations in the immune protein composition of mother’s milk reflects subsistence pattern

Abstract: Lay SummaryAdaptive immune proteins in mothers’ milk are more variable than innate immune proteins across populations and subsistence strategies. These results suggest that the immune defenses in milk are shaped by a mother’s environment throughout her life.Background and objectivesMother’s milk contains immune proteins that play critical roles in protecting the infant from infection and priming the infant’s developing immune system during early life. The composition of these molecules in milk, particularly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 122 publications
2
21
0
Order By: Relevance
“…Additionally, the analysis of milk samples from more than 20 mothers in each group according to the duration of lactation was performed. Moreover, in contrast to the latest reports of Klein et al ( 48 ), who adopted triple–quadrupole time-of-flight mass spectrometry for immunoglobulin determinations, we used highly specific immunochemical ELISA methods, which we believe are better because they are cheaper, faster, more accessible, and can be routinely used in labs in milk banks, after appropriate adaptation, to characterize the immunological status of donor milk. The limitations of our study are its being a single-center, non-randomized controlled study and there being no short- and long-term health follow-up of the infants of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the analysis of milk samples from more than 20 mothers in each group according to the duration of lactation was performed. Moreover, in contrast to the latest reports of Klein et al ( 48 ), who adopted triple–quadrupole time-of-flight mass spectrometry for immunoglobulin determinations, we used highly specific immunochemical ELISA methods, which we believe are better because they are cheaper, faster, more accessible, and can be routinely used in labs in milk banks, after appropriate adaptation, to characterize the immunological status of donor milk. The limitations of our study are its being a single-center, non-randomized controlled study and there being no short- and long-term health follow-up of the infants of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Milk may be a more specific niche than the gut, as it appears that milk is enriched in particular bacterial taxa from the gut and suppressed in others (Ascinar et al, ; Jin, Hinde, & Tao, ). Only specific bacteria may be trafficked to the mammary glands by EMT or colonize milk from infant retrograde flow, which may be a conserved evolutionary pathway regardless of population origin (Klein et al, ; ).…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study across seven ecologically and economically diverse populations, Klein et al. () demonstrated that acquired immune protein composition—which reflects both recent and lifelong maternal disease exposures—exhibited greater interpopulation variation than did innate composition. Miller () similarly found differences in levels of anti‐inflammatory milk bioactives between US and Kenyan (Ariaal) mothers, which further predicted differences in infant growth outcomes.…”
Section: Relational Dynamics Influencing Biology and Behaviormentioning
confidence: 99%